2015
DOI: 10.1017/jrr.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Sex, Sexual Orientation, and the Necessity of Physical Attractiveness and Social Level in Long-Term and Short-Term Mates

Abstract: In comparison to biological sex differences and mate preferences, differences in sexual orientation and mate preferences have received limited attention in the literature. The aim of the current experiment was to explore the relationship between biological sex and sexual orientation on the necessity of a longterm and short-term mate's physical attractiveness and social level. Three hundred and seven participants recruited from an Australian university and the wider community completed an online questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although the mating strategies of homosexual and heterosexual men and women are not considered to differ ( Symons, 1979 ), some research has shown differences in mate preferences for homosexual and heterosexual women ( Bailey, Gaulin, Agyei, & Gladue, 1994 ). As such, although homosexual men’s and women’s mate preferences may be fundamentally similar to their heterosexual counterparts, this similarity should not be assumed ( March, Grieve, & Marx, 2014 ). Future research would benefit from exploring mate preferences of individuals other than those with a heterosexual orientation in these relationship paradigms (i.e., booty calls, friends with benefits, and fuck buddies).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mating strategies of homosexual and heterosexual men and women are not considered to differ ( Symons, 1979 ), some research has shown differences in mate preferences for homosexual and heterosexual women ( Bailey, Gaulin, Agyei, & Gladue, 1994 ). As such, although homosexual men’s and women’s mate preferences may be fundamentally similar to their heterosexual counterparts, this similarity should not be assumed ( March, Grieve, & Marx, 2014 ). Future research would benefit from exploring mate preferences of individuals other than those with a heterosexual orientation in these relationship paradigms (i.e., booty calls, friends with benefits, and fuck buddies).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it would also be prudent to establish the effects of gender roles and SES on short‐term mate preferences for men and women of differing sexual orientations. Recent studies (e.g., March, Grieve, & Marx, ) have shown that mate preferences for men and women of heterosexual, homosexual, and bisexual orientations differ, and as such should not just be assumed to be equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that people go changing progressively their preferences when they grow up, involving in long-term relationships [ 22 ]. Regarding sexual orientation, individuals who are part of sexual minorities, especially men, are much more likely to have short-term relationships than heterosexual people [ 32 ], perhaps because they are looking for a partner for different reasons to the procreation [ 33 ].…”
Section: Introductionmentioning
confidence: 99%